2015
DOI: 10.1111/pbi.12336
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA transcriptome of plants

Abstract: Summary Since their discovery more than two decades ago, animal long noncoding RNAs (lncRNAs) have emerged as important regulators of many biological processes. Recently, a large number of lncRNAs have also been identified in higher plants, and here, we review their identification, classification and known regulatory functions in various developmental events and stress responses. Knowledge gained from a deeper understanding of this special group of noncoding RNAs may lead to biotechnological improvement of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
208
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(217 citation statements)
references
References 172 publications
(223 reference statements)
1
208
0
8
Order By: Relevance
“…This may not be due only to the fact that most plant lncRNAs are expressed at low levels and their expression may be confined to specific cell types or specific conditions, but also to the fact that plant lncRNAs are not evolutionarily conserved in general (Liu et al, 2012(Liu et al, , 2015a(Liu et al, , 2015b.…”
Section: Drir Is a Novel Lncrna Regulating Plant Tolerance To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not be due only to the fact that most plant lncRNAs are expressed at low levels and their expression may be confined to specific cell types or specific conditions, but also to the fact that plant lncRNAs are not evolutionarily conserved in general (Liu et al, 2012(Liu et al, , 2015a(Liu et al, , 2015b.…”
Section: Drir Is a Novel Lncrna Regulating Plant Tolerance To Droughtmentioning
confidence: 99%
“…The dual transcription of APOLO regulates the formation of a chromatin loop encompassing the promoter of PID and, thus, affects auxin transport . Liu et al (2015b) suggested that lncRNAs may participate in ABA-induced complex assembly and the relocalization of RNA-BINDING PROTEIN. However, lncRNAs involved in the ABAmediated stress response are still unknown.…”
Section: Drir Regulates Aba-mediated Responses To Drought and Salt Stmentioning
confidence: 99%
“…It could also be due to the great depth of reads used for assembly (a total 1,015,845,414 reads). Even though the PacBio data included the same internodal RNAs as the de novo dataset, it has been through different library preparation, where the cDNA were produced from only polyA RNAs, which should be mostly mRNA and long non-coding RNAs with a polyA tail (Liu et al, 2015). The comparison of transcripts between the two assemblies suggests that the common transcripts between the two assemblies would mostly be polyA RNAs, while the transcripts unique to PacBio (38%) could be rare transcripts that come from the normalization process and wider tissue coverage, and those unique to de novo assembly (33%) could be attributed to other types of RNAs in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that de novo transcript contigs could be a good resource for studying the diversity of non-coding RNAs (Lv et al, 2016). Long non-coding RNAs are RNAs, longer than 300bp, that do not encode proteins (do not have ORF ≥100 aa) potentially play important roles in gene regulation of eukaryotic cells (Liu et al, 2015). Their numbers, characteristics and genetic patterns in the genome still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately at the present the ncRNA is still in their early stages and just some mammalian entries were uploaded to IncRNA database (Laurent et al, 2015). Up to now, the only plant that has received some attention is Arabidopsis thaliana where 13,000 RNAs were found transcribed from intergenic regions (Liu et al, , 2015a Gene ontology provides a systematic language in three key biological domains shared by all organisms: molecular function, biological process and cellular component to unify the representation of gene features across all species (Gousset et al, 2005). GO terms are structured as a graph and can be distributed in levels.…”
Section: Annotation Of S Incanum and S Aethiopicum Transcriptomesmentioning
confidence: 99%